THEORETICAL AND CONCEPTUAL FOUNDATIONS OF SPATIAL DEVELOPMENT OF REGIONS - Имашев, Эдуард (Вестник ЗКУ, 2024)
The paper presents the results of a study of fundamental scientific works and scientific-analytical studies of foreign and domestic economic geographers and economists, revealing the theoretical and conceptual foundations of the spatial development of regions. The article shows the essence and features of the influence of the following theories and concepts on the spatial development of the region: the theory of central places; concepts for the development of problem (crisis, depressed, marginal) areas; theories of diffusion of innovations; concepts of poles and centers of growth (“polarized development”); theories of territorial production complexes; Japanese concept of technopolises; theories of geographical (territorial) industrial clusters; Russian concept of polarized development. Based on the considered theories and concepts, the goals and objectives of the spatial development of regions are formulated. It is concluded that these theories and concepts can contribute to the effective territorial organization of the economy and population, the spatial development of the regions of Kazakhstan based on the transformation and modernization of regional territorial socio-economic systems.